2014
DOI: 10.1155/2014/690315
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Perception and Healthcare Seeking Behavior of Pneumonia Children in Rural Bangladesh

Abstract: We describe mothers' perception about signs and symptoms, causes of the illness, and healthcare seeking behaviors related to pneumonia and express the major modifiable barriers to seeking timely treatment when their under-5 children had pneumonia in rural Bangladesh. Using focus group discussion, we understood mothers' perception and healthcare seeking behavior of childhood pneumonia. Although mothers described pneumonia as a serious life threatening disease in young children but most of the mothers (n = 24) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 22 publications
8
44
0
1
Order By: Relevance
“…Mothers in the rural areas reported lower likelihood of seeking healthcare for their children's illnesses as compared to their counterparts in the urban areas. This result is consistent with previous ndings from Ethiopia [34] and Bangladesh [35] where mothers in the rural areas reported low healthcare seeking behavior for their children's illnesses.…”
Section: Resultssupporting
confidence: 92%
“…Mothers in the rural areas reported lower likelihood of seeking healthcare for their children's illnesses as compared to their counterparts in the urban areas. This result is consistent with previous ndings from Ethiopia [34] and Bangladesh [35] where mothers in the rural areas reported low healthcare seeking behavior for their children's illnesses.…”
Section: Resultssupporting
confidence: 92%
“…This lack of knowledge and poor perceived seriousness may be related to the high number of mothers without any formal education or any awareness about pneumonia. In accordance with our findings, poor knowledge about pneumonia (71%) has been reported in another developing country, Bangladesh (18). A UNICEF/WHO report showed that only 1 in 5 care givers knew the 2 tell-tale or indicative symptoms of pneumonia: fast breathing and difficult breathing (2).…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that repeated pneumonia in a child was not uncommon in the present study. Similar findings have been reported in Bangladesh and Peru (18,21); this may be attributed to persistent exposure to environmental risk factors such as exposure to tobacco smoke (26,27), overcrowding (28) or indoor and outdoor pollution (29,30).…”
Section: Discussionsupporting
confidence: 83%
“…Oleh karena itu, perawatan berfokus keluarga menjadi konsep utama perawatan anak selama hospitalisasi (Nurhaeni, Sutadi, Rustina, & Supriyatno, 2011). Keluarga, khususnya ibu, merupakan orang yang paling dekat dengan anak dan diharapkan mampu merawat anak selama di rumah, memenuhi kebutuhan, menyelesaikan masalah, dan menggunakan sumber-sumber yang tepat dalam memenuhi kebutuhan kesehatan keluarga (Ferdous, et al, 2014).…”
Section: Pendahuluanunclassified